Modulation of inflammatory pathways in ischemic stroke rats by hypoxia-primed umbilical cord mesenchymal stem cells (UC-MSCs): Implications for IFN-γ and IL-10 signaling - Fahreza, Rakha; Setiawan, Eko; Trisnadi, Setyo; Putra, Agung; Hidayah, Nurul; Fikriya Novita Sari; Ibrahim, Sugeng (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Ischemic stroke is a major global cause of disability and mortality. Inflammation plays a central role in its pathogenesis, characterized by elevated pro-inflammatory cytokines such as IFN-γ and reduced anti-inflammatory cytokines like IL-10. Mesenchymal stem cells (MSCs), especially those derived from the umbilical cord (UC-MSCs), exhibit enhanced immunomodulatory potential when preconditioned under hypoxia. This study aims to evaluate the effect of hypoxic-preconditioned UC-MSCs administration on IFN-γ and IL-10 levels in an ischemic stroke rat model. This in vivo experimental study employed a randomized posttest-only control group design with four groups of male Wistar rats (n=6 each), ranging from healthy controls, untreated group to stroke-induced groups treated with hypoxic UC-MSCs at different doses (1.5x106 and 3x106). IFN-γ and IL-10 levels in brain tissue of each group were measured via ELISA. Significant reduction in IFN-γ and elevation in IL-10 were observed in UC-MSC-treated groups, particularly at the 3×10⁶ cell dose compared to the untreated ischemic group (p<0.05). Hypoxic UC-MSCs reduce post-stroke inflammation by lowering IFN-γ and enhancing IL-10, indicating a promising immunomodulatory potential.